KEBERTAHANAN PEREMPUAN PEDAGANG ACUNG PADA KAWASAN PARIWISATA KINTAMANI, BALI (Jurnal Ilmiah Pariwisata, 2015)
Kintamani as a tourist destination that has been introduced by a German author named Gregor Krause on 1912 has implications for the emergence of the community who work as vendor. The presence of tourists in Kintamani considered to require something that is memorable, so souvenirs as a product that easy to brought by travelers as a important thing to be sold to tourists. In the development of the community who work as a vendor mostly women. Presence of women in the area of tourism in Kintamani very interesting to observe, their practice in the public sector exceeded the role of men. At this writing, the survival of women as a vendor analyzed by qualitative descriptive to know the motive of their existence, even though their sales declined, but they still survive as a vendor. In findings in the field, in addition to the economic motive to strengthening the economic basis of the family, the social motives to actualize themselves in society also as their reason as vendor.
Keywords: Women, Survival, Vendor, Tourism, Kintamani